(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Despite the many researches in the Qur’an, its diversity, and the multiplicity of its methods, it is still an inexhaustible resource, its miraculousness and wonders. The motive for choosing the topic (the effect of the repetition of the pronoun in the endowment and the initiation) is because it is in one of the links of grammar and has a connection with the sciences of the Holy Qur’an; and it reveals its impact on the endowment and the beginning, so I opened it with an introduction in which I mentioned the reason for choosing the topic of the research, after which a prelude to the definition of the terms of the title of the research, followed by three demands; I dealt within the first requirement: the unification of the repetition of pronouns and their dismantling, and in the second: the repetition of the pronoun on the advanced or the late, and in the third: the repetition of the pronoun on the nearest or farthest and the impact of this on the endowment and the beginning. The research ends with Aconclusion which includes the most important resuhts, for instance, the poronoun of the endowment has agreat significance in explaining the place of the endowment, and that the scholars preferred the place of the endowment, taking into account the principle that the order of pronouns takes precedence over dismantling, and the principle of the return of the pronoun to the closest mentioned, and the principle of the permissibility of the pronoun returning to a later pronunciation if there is a presumption to help it, and that the pronoun determines the endowment and does not specify its type.